Preconcentration of Copper(II) in Water Samples Using Polyurethane Foam/2-(6’-Ethyl-2’-benzothiazolylazo)chromotropic Acid - Moghimi, Ali; Tajodini, Nilofar (Asian Journal of Chemistry, 2010)
In this work, polyurethane foam (PUF) loaded with 2-(6'-ethyl-2'-benzothiazolylazo)chromotropic acid (Ethyl-BTANC) was packed in a minicolumn and it was used in an on-line preconcentration system for cadmium and lead determination. Optimum hydrodynamic and chemical conditions for metal sorption were investigated. The effects of several foreign substances on the adsorption of copper(II) was also reported. The enrichment factor obtained was 37 (Cu) for 180 s preconcentration time. The proposed procedures allowed the determination of metals with detection limits (3σ) of 4.11 μg L-1 (0.10 and 0.52 μg g-1 of solid sample) for copper(II). The precision of the procedures was also calculated: 3.3 (Cu 10 μg L-1). The accuracy of the procedure was checked by analysis of the certified reference materials. copper(II) contents in water samples (sea water and tap water) were determined by applying the proposed procedure.